Demokratisasi Relasi Sipil–Militer pada Era Reformasi di Indonesia - Kardi, Koesnadi (Masyarakat: Jurnal Sosiologi, 2014)
Indonesia’s military reform resulted cultural, structural, doctrinal and organizational changes. But those changes are not fundamental enough to build democratic civil–military relation that relies on civilian supremacy. The process of military reform in Indonesia showed us that the success of democratization of civil–military relation depends on institutional setup of the military related to civilian institutions’ persistency, guidance, and initiative. This study used Peter D. Feaver’s theory of “principal-agent” to show that the lack of civilian institutions’ coherence and resoluteness caused persisting problems to the Indonesia’s military reform under democratic system. Civilian supremacy in Indonesia appears to be relied on “voluntary subordination” of the military rather than effective civilian control over the military. Hence, instructive policies and legal basis become very important to yield a complete subordination of the military to the civil within democratic system. This argument confronts the existing studies, especially those with political perspective, that tended to accept the idea that military supremacy in politics is needed to build a strong nation state and to uphold the constitution. This study uses qualitative method with data collected by interviewing some key figures in military and civilian institutions.